Into the Great Unknown : Stress Testing with Weak Data - Ong, Li (IMF Working Papers; Working Paper ;, 2010)
Stress testing has become the risk management tool du jour in the wake of the global financial crisis. In countries where the information reported by financial institutions is considered to be of sufficiently good quality, and supervisory and regulatory standards are high, stress tests can be of significant value. In contrast, the proliferation of stress testing in underdeveloped financial systems with weak oversight regimes is fraught with uncertainties, as it is unclear what the results actually represent and how they could be usefully applied. In this paper, problems associated with stress tests using weak data are examined. We offer a potentially more useful alternative, the "breaking point" method, which also requires close coordination with on-site supervision and complemented by other supervisory tools and qualitative information. Excel spreadsheet templates of the stress tests presented in this paper are provided.